2015
DOI: 10.1016/j.landusepol.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Are preserved farms actively engaged in agriculture and conservation?

Abstract: Abstract:This study addresses the question of whether farms enrolled in land preservation programs are actively engaged in agricultural or conservation activities. Data are drawn from an original survey administered to preserved farm owners in the states of New Jersey, Maryland, and Delaware in 2011. "Actively engaged" is defined as investment in conservation projects, buildings, equipment, or irrigation since the land was preserved. Affirmative answers to the survey's investment questions range from a low of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Following the literature, which generally hypothesizes positive relationships between farm characteristics and conservation adoption, we posit a positive hypothesis for all subcategories except for soil quality (table 5). Prior research indicates, for example, that the size of the farm (acres) increases adoption of many types of conservation practices including conservation tillage (Belknap and Saupe 1988), water conservation (Dorfman 1996;Gottlieb et al 2015), cover crops (Dunn et al 2016), nutrient management (Caswell et al 2001), and rotational grazing (Gillespie et al 2007). Land tenure is considered an important construct (Soule et al 2000); when farm operators own the land they manage, studies have observed an increase in the level of adoption of a number of practices including nutrient management (Bosch et al 1995;Khanna 2001), pest management (Caswell et al 2001), and soil management practices (Lichtenberg 2004).…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%
“…Following the literature, which generally hypothesizes positive relationships between farm characteristics and conservation adoption, we posit a positive hypothesis for all subcategories except for soil quality (table 5). Prior research indicates, for example, that the size of the farm (acres) increases adoption of many types of conservation practices including conservation tillage (Belknap and Saupe 1988), water conservation (Dorfman 1996;Gottlieb et al 2015), cover crops (Dunn et al 2016), nutrient management (Caswell et al 2001), and rotational grazing (Gillespie et al 2007). Land tenure is considered an important construct (Soule et al 2000); when farm operators own the land they manage, studies have observed an increase in the level of adoption of a number of practices including nutrient management (Bosch et al 1995;Khanna 2001), pest management (Caswell et al 2001), and soil management practices (Lichtenberg 2004).…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%
“…Asymmetric tendencies were also .0000. Related to Models 2, 4, and 6 was 4-variate probit (with some different variables), which was previously reported in Gottlieb et al (2015), but the results were not compared to the three other regressions as they were herein. Reserve categories of the indicator variables in all models are: Owner-nonoperator, Heir-nonrelative.…”
Section: Farming Reinvestments: First-generation Investment Patternsmentioning
confidence: 99%
“…There is agreement that the coordination mechanism through which farmers have access to land is determinant. Numerous articles also concern PDRs (Gottlieb et al, 2015;Liu & Lynch, 2011;Schilling, Attavanich, Sullivan, & Marxen, 2014;Towe, Nickerson, & Bockstael, 2008), which are currently neither full nor long-term RAs to preserve farmland. Therefore, evaluating the LFRAs' effectiveness in reaching the goal of preserving farmland from land use changethrough urbanization or even simply farming abandonment-requires an economic analysis of the lease arrangements they induce.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies assessing the agricultural effects of RAs on preserving farmland have addressed land trusts without analyzing the effects on the agricultural economy (Dissart, 2006;Parker, 2004). Numerous articles also concern PDRs (Gottlieb et al, 2015;Liu & Lynch, 2011;Schilling, Attavanich, Sullivan, & Marxen, 2014;Towe, Nickerson, & Bockstael, 2008), which are currently neither full nor long-term RAs to preserve farmland. Our article aims at helping fill this gap by providing an economic approach to contracts provided by LFRAs.…”
Section: Introductionmentioning
confidence: 99%